The Effect of Electricity Supply on the Performance of Small and Medium-Scale Enterprises in Nigeria: A Case Study of Calabar South and Calabar Municipality of Cross River State - Christian E.Bassey; Imoh Kingsley Ikpe (International Journal of Engineering and Management Research, 2021)
This research work analyzed the comparative study of the effect of electricity supply on the performance of small and medium-scale enterprises in Calabar South and Calabar Municipality,using small and medium scale businessmen and women as well as power holding company staff. The objectives of this study to analyze the comparative study of the effect of electricity supply on the performance of small and medium-scale enterprises in Calabar South and Calabar Municipality.The survey research design was adopted and a twelve (12) item structured questionnaire was used to obtain a sample size of 248 small and medium scale business owners and power holding staff randomly selected from the population. The results of the study revealed that there is a significant effect of electricity supply on the performance of small and medium-scale enterprises in Calabar South and Calabar Municipality. The results further revealed that insufficient electricity supply significantly affect the performance of small and medium-scale enterprises in Calabar South and Calabar Municipality.The study concludes that there are enormous difficulties being experienced by businesses in Cross River State and other parts of Nigeria due to inadequate and unreliable electric power supply. Thus an inadequate and unreliable supply of electricity imposes costs and therefore constrained firms’ operational performance as firms suffer high overhead cost due to the deficient electricity supply from the national grid. The study recommends that the Nigerian government needs to consider the issue of power supply reliability very seriously by facilitating both private and public investment in electricity infrastructure.